Coach perceptions of FA youth heading guidance: an online survey - Austin, K.; Lauder, M. A.; Smith, N. A. (Science and Medicine in Football, 2023)
Concerns surrounding the safety of heading within football led the English Football Association (FA) to implement guidelines for youth football participants in February 2020. Information on coach perceptions of guidelines can help to evaluate their suitability.From aninitial 1383 clubs emailed, a total of 351 respondents from English teams spanning ages U12-U18 completed an online survey between August 2020 and January 2021. Questions included their familiarity with and perceptions of youth guidelines, as well as how they approach heading within training. Information was also gathered on perceived heading frequency within training and matches. 31.1% of respondents were either unaware of guidelines or how they relate to their team. Only 4.8% of respondents did not agree with guidelines. For most respondents (60.1%), heading frequency in training was low (between 0 and 5 headers for the whole team per session), with 71.1% of respondents reporting that heading exposure would stay the same in response to guidelines. Most participants were aware of and agree with FA youth heading guidelines, however the majority think their training will not be influenced by guidelines, questioning their applied usefulness. Regardless of guidelines, coach reported heading frequency within training and matches appears to be low.